Genetics and the unsettled past : the collision of DNA, race, and history - Wailoo, Keith; Nelson, Alondra; Lee, Catherine, 1971- (Rutgers studies in race and ethnicity., 2012)
Genetics and the Unsettled Past considers the alignment of genetic science with commercial trends in genealogy, with legal and forensic developments, and with pharmaceutical innovation to examine how these trends lend renewed authority to biological understandings of race and history. Essays by scholars across a wide range of disciplines-biology, history, cultural studies, law, medicine, anthropology, ethnic studies, sociology-explore the emerging and often contested connections among race, DNA, and history.